Türkçe öğretmenlerinin özel alan yeterlikleri: Bir durum belirleme çalışması - Kübra ŞENGÜL; Ercan ALKAYA (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
In this study a descriptive survey model is used in order to determine the Turkish language teachers’ opinions regarding their competencies in the special field of Turkish Language Teaching. The study sample of the Turkey Statistical Institute (TSI) according to the classification introduced by statistical regional units from each of the 12 statistical regions in the province, a total of 12 is a Turkish teacher who served 579. A questionnaire that has been designed by the Ministry of Education is used as a tool and personal information form for data collection. The questionnaire consists of 5 major competency areas 25 sub-competencies and 165 performance indicators in the special field of Turkish Language Teaching. As a result, “Turkish Teacher’ Competencies for Special Area” according to the on average, Turkish teachers “partially sufficient” to be determined. They also seeing Turkish educational process planning and organizing an “adequate”; students’ language skills from an “adequate”; students’ language development, monitoring and evaluation, “partially sufficient”; school, family and community cooperation in making “partially sufficient”; in providing professional development in the field of Turkish “partially sufficient” to be determined